Avaliação in vitro dos efeitos da Anadenanthera colubrina (Vell.) Brenan sobre fatores de virulência de Candida albicans, modulação da interação Candida-hospedeiro e regulação da atividade imunomodulatória - Maia, Carolina Medeiros de Almeida (2020)
OBJECTIVE: This study evaluated in vitro the antifungal activity of Anadenanthera colubrina (Vell.) Brenan barks extract on Candida spp., its effects on virulence factors of Candida albicans, modulation of immune response through C. albicans-host interaction and regulation from anti-inflammatory activity. MATERIAL AND METHOD: The antifungal activity was evaluated by Broth Microdilution Method on reference strains of Candida spp. (C. albicans, C. glabrata, C. tropicalis, C. dubliniensis). Anti-biofilm effect was determined on C. albicans mature biofilm and quantified by Colony Forming Units/mL of biofilm dry weight (CFU/mL/g). Activities from proteinase and phospholipase enzymes were determined through azocasein and phosphatidylcholine assays, respectively. The cytotoxicity was assessed by Cell Titer Blue viability assay on human gingival fibroblasts (HGF ATCC® CRL-2014) and on human monocytes (THP-1 ATCC® TIB-202). The coculture model of C. albicans-HGF was analyzed by SEM (Scanning Electron Microscopy) and fluorescence microscopy, by gene expression of the enzymes released by C. albicans (SAP-1, PLB-1) and the host's inflammatory cytokines (IL-6, IL-8, IL-1β, IL-10) evaluated by RT-PCR; and by the release of cytokines, assessed by Luminex. The inflammation model was assessed through THP-1 cells exposed to LPS (Lipopolysaccharide), with evaluation from gene expression and levels of production of inflammatory cytokines (IL-8, IL-1β and IL-10), by RT-PCR and Luminex, respectively. Simple Western (WES Simple) was performed to identify the expression of key proteins of NF-κB and MAPK transduction signaling pathways (NF-κB, p-38, p-NF-κB and p-p38). The phytochemical characterization of the extract was assessed by HPLC-ESI-MSn (High-Performance Liquid Chromatography with Electrospray Ionization Mass Spectrometric) and LC-HRESIMS (High Resolution Electrospray Ionization Mass Spectrometry). RESULTS: Extract presented fungistatic effect with MIC<15.25 µg/mL against Candida strains tested. Biofilm and proteolytic activity were significant reduced at 312.25 µg/mL extract concentration. For cell viability assay, the extract presented LD50 = 423.3 µg/mL for HGF cell line, and LD50 = 978.7 µg/mL for THP-1. Coculture microscopies demonstrated a substantial decreased in C. albicans growth and minimal toxicity against host cells. Gene expressions of SAP-1/PLB-1 were significantly down-regulated and host immune response was modulated by a significant decreased on IL-6 and IL-8 pro-inflammatory cytokines secretion. Upon LPS stimuli, gene expression and cytokines production of IL-1β and IL-10 were down and up-regulated, respectively. The extract is involved on TRL4-related NF-κB/MAPK pathways through phosphorylation of p38 and NF-κB, with decreased in the signal intensity. Extract itself did not induce inflammatory response. Phytochemical analysis showed a phenolic profile with presence of flavonoids, cathechins, procyanidins and tannins. CONCLUSION: A. colubrina extract presented antifungal activity on Candida strains, low cytotoxicity, antibiofilm and anti-proteolytic enzyme effects against C. albicans, with modulatory effects on the host immune response in front of infection and anti-inflammatory activity.